Virtual Reality for Assessing Body Image: The Body Image Virtual Reality Scale (Bivrs) - Riva, Giuseppe; Melis, Luca; Bolzoni, Mirco (International Journal of Virtual Reality, 1996)
BIVRS, Body Image Virtual Reality Scale, is a prototype of a diagnostic freeware tool designed to assess cognitive and affective components of body image. It consists of a non- immersive 3D graphical interface through which the patient is able to choose between 7 figures which vary in size from underweight to overweight. The software was developed in two architectures, the first (A) running on a single user desktop computer equipped with a standard virtual reality development software, and the second (B) split into a server (B1) accessible via Internet and actually running the same virtual ambient as in (A), and a VRML client (B2) so that anyone can access the application. The importance of a virtual reality based body image scale relies on the possibility to rapidly test one’s perceived body image in better and different ways. It also provides an opportunity to easily develop a trans-cultural database on body image data. Furthermore, the possibility of using 3D can improve the effectiveness of the test because it is easier for the subject to perceive the differences between the various proposed silhouettes.